Revisión sistemática ventajas y desventajas de las técnicas de prototipeado rápido (pr): estereolitografía (sla) la sinterización selectiva por láser (sls) y el modelado por deposición fundida (fdm) - Pazmiño Zúñiga, Alex Sebastián (2025)
Rapid prototyping techniques are a set of manufacturing methods that transform 3D digital designs into physical models transform 3D digital designs into physical models, thus speeding up the development process. Objective To verify the advantages and disadvantages of each rapid prototyping technique, by means of a review of updated bibliography, to select the best one. Materials and Methods A qualitative data analysis was carried out, where we relied on high impact artic les or journals in order to have a veracity of the content. high impact articles or journals in order to have a veracity of the content, where we used the PRISMA METHOD. The databases from which we will select information are PubMed, ScienceDirect and Goog le Scholar from the last 7 years in order to collect valid information according to the inclusion and exclusion criteria. Results The final search concluded with a total of 57 articles, of which 15 were selected for the study after excluding selected for the study after excluding documents for not being retrievable, for being duplicate documents, for not being related to rapid prototyping techniques, for being another type of study, for being other type of study, date of publication and unrelated to the t opic. Highlighting that stereolithography ( is the best rapid prototyping technique due to its characteristics. its characteristics. Conclusions Stereolithography ( although a little more expensive, is the best rapid prototyping technique that c an be used to rapid prototyping technique that can perform and meet parameters such as accuracy, detail and manufacturing time compared to other printing technologies. Keywords: stereolithography ( selective laser sintering ( fused deposition modelling ( fused deposition ( fused deposition modelling ( rapid prototyping (